MEASURING HPV VACCINATION AWARENESS: AN ANALYTICAL STUDY AMONG YOUNG WOMEN - Pathak, Alisha; Deb, Anindya; Joshi, Anjali; Anand, Ayush (ShodhKosh: Journal of Visual and Performing Arts, 2024)
“Despite being completely preventable, cervical cancer is the second most common type of cancer for Indian women. The mortality rate for India due to cervical cancer is higher than the global average. This paves a way for massive screening and immunization programs by the government. However, lack of awareness about the causes and preventive behaviours for cervical cancer among the population is prevalent. Vaccination as well as screening programs are bound to be unsuccessful unless the target population is vigilant about the severity of this disease. This paper uses online survey method to measure the HPV vaccination awareness and role of media in propagating HPV vaccination messages among young women. The major objectives of this study are to measure the level of awareness, understand the role of media in stimulating HPV vaccination awareness and find the factors that stop women from getting vaccinated. A total of 88 responses were received and analyzed using descriptive statistics. The findings of this study suggest that not only in marginalized communities but also in well empowered young women, the level of awareness for HPV vaccination is low. The media has so far not been utilized optimally for propagating the messages and alongside, lack of awareness, unavailability and high cost of vaccines are important factors that inhibit the uptake of vaccination by young women in India.”